Innovation and willingness to export: Is there an effect of conscious self-selection? - Mohammad Movahedi; Kiumars Shahbazi; Olivier Gaussens (Economics: The Open-Access, Open-Assessment E-Journal, 2017)
This paper presents an analysis of the crucial relationship between innovation, productivity, and export in Small and Medium Enterprises (SMEs). The primary aims of this study are to evaluate the role of innovation in the premium export and test the hypothesis of firm conscious self-selection on willingness to export. To this end, the authors used their database of SMEs, obtained from the survey conducted in the IDEIS project, which provides highly pertinent information on innovation and export areas. Based on the aforementioned database, the authors evaluate apparent premium of exportation and innovation. In addition, they demonstrate the effectiveness of the export premium for high exportation firms that implement process and organization innovations. Finally, the authors analyse the effect of conscious self-selection from the export process that transforms an intention to export into the capacity to export in short term. The conscious self-selection to export is revealed by simultaneously endogeneizing productivity and innovation output based on recursive non-linear model.
Keywords: C14; C35; D22; F12; O31; 330; export process; productivity; export premium; innovation premium